Comparison of athletic movement between elite junior and senior Australian football players. Issue 13 (2nd July 2016) - Woods, Carl T.; McKeown, Ian; Haff, Gregory G.; Robertson, Sam
ABSTRACT: This study compared the athletic movement skill between elite Under-18 (U18) Australian football (AF) and senior Australian Football League (AFL) players. The U18 sample ( n = 13; 17.7 ± 0.6 years) were representatives of an elite talent development programme. The AFL players were classified accordingly; Group 1 (1–4 AFL seasons; n = 20; 21.2 ± 1.9 years) and Group 2 (>5 AFL seasons; n = 14; 26.3 ± 2.6 years). Participants performed an athletic movement skill assessment, inclusive of five foundational movements. Each movement was scored across three assessment points using a three-point scale. Total score for each movement (maximum of nine) and overall score (maximum of 63) were used as criteria. Multivariate analysis of variance (MANOVA) was used to test the effect of developmental group (three levels) on the criteria. Receiver operating curves were built to examine the discriminant capability of the overall score. A significant effect of developmental group was noted, with the U18 sample having a lower mean total score for four of the five movements. Overall scores of 49/63 and 50/63 discriminated the elite U18 sample from Group 1 and Group 2, respectively. U18 players may have less developed athletic movement skills when compared to their senior AFL counterparts.